Influence of Bidirectional Impact Loading on Anomalously Low-Friction Effect in Block Rock Media - Liping Li; Weijun Li; Jupeng Tang; Jiaqing Lv (Advances in Civil Engineering)
The anomalously low-friction effect is a key scientific problem in deep mining. The deep coal rock media is usually a block structure with joint fracture. When the deep block coal rock is subjected to repeated strong dynamic impact caused by long-term excavation activities, the anomalously low-friction effect will occur, resulting in dynamic disasters such as rock bursts. Taking granite block rock media as research object and using bidirectional impact loading to simulate the dynamic disturbance of rock media, a numerical model was established. The vertical acceleration and the horizontal displacement on working block media were defined as the characteristic parameters of the anomalously low-friction effect. The effects of delay time and horizontal impact loading amplitude and frequency on the characteristic parameters under bidirectional impact loading were examined by numerical simulation. The generation and variation of the anomalously low-friction effect of block rock media subjected to bidirectional impact loading were presented. The results show that the delay time has a significant effect to the vertical acceleration amplitude and horizontal displacement on the working block media under bidirectional impact loading. There exists a delay time threshold; when reach to the threshold, quasiresonance and the anomalously low-friction effect on block media will easily occur. With the increase in horizontal impact amplitude, the residual horizontal displacement on the working block media also increases by power function, while it decreases by power function with the increase of horizontal impact loading frequency. Finally, this study denotes that it is great significance to investigate the bidirectional impact loading in order to capture the mechanism of anomalously low-friction effect.